Letter from Caldwell K. Biddle to James Curtis Booth, February 8, 1856 - Biddle, Caldwell K. (1856)
A follow up to Biddle's letter of February 6.
Keywords: Booth, James Curtis, 1810-1888; Chemistry teachers; University of Pennsylvania